Budget Semi-Elasticity and its Impact on Debt Flexibility in the Context of the Debt Brake - Philipp Heimberger; Bernhard Schütz (Wirtschaftsdienst)
Abstract The debate on the cyclical adjustment procedure of the debt brake has focused on problems with regards to potential output. The second key determinant of the cyclical budget component, however, has been neglected: the semi-elasticity of the budget balance, which measures the response of federal revenues and expenditures to the business cycle. We analyse the sensitivity of estimates of the semi-elasticity with respect to data inputs and model specifications. Our results highlight estimation uncertainties that affect how much the federal government is allowed to borrow under the debt brake.